Influence of Different Cations of N3 Dyes on Their Photovoltaic Performance and Stability - Luísa Andrade; Shaik M. Zakeeruddin; Mohammad K. Nazeeruddin; Helena Aguilar Ribeiro; Adélio Mendes; Michael Graetzel (International Journal of Chemical Engineering)
The N3 dye was modified by substituting two of its protons by potassium or sodium cations. The performance and stability of dye-sensitized solar cells incorporating the new dyes were evaluated under light soaking (1000 W⋅m-2) at 50∘C. Photocurrent measurements demonstrated that proton substitution by potassium cations rends the system more stable. Further characterization of the potassium-based devices was performed by electrochemical impedance spectroscopy to investigate the charge-transfer phenomena occurring at the different interfaces of the cells.